2024
DOI: 10.1029/2023jd039370
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Unsteady Stable Boundary Layer With a Stochastic Stability Equation

Vyacheslav Boyko,
Nikki Vercauteren

Abstract: Turbulence in very stable boundary layers is typically unsteady and intermittent. The study implements a stochastic modeling approach to represent unsteady mixing possibly associated with intermittency of turbulence and with unresolved fluid motions such as dirty waves or drainage flows. The stochastic parameterization is introduced by randomizing the mixing lengthscale used in a Reynolds average Navier‐Stokes (RANS) model with turbulent kinetic energy closure, resulting in a stochastic unsteady RANS model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Vercauteren et al (2019a) found different regimes of influence by submeso motions associated with different anisotropies of the Reynolds stress tensor. Boyko and Vercauteren (2023), Kaiser et al (2024), and Boyko and Vercauteren (2024) used different approaches to include randomization in models to simulate intermittency of the turbulence and potential abrupt transitions. Van de Wiel et al (2012) determined the minimum wind speed required for maintaining fully developed turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Vercauteren et al (2019a) found different regimes of influence by submeso motions associated with different anisotropies of the Reynolds stress tensor. Boyko and Vercauteren (2023), Kaiser et al (2024), and Boyko and Vercauteren (2024) used different approaches to include randomization in models to simulate intermittency of the turbulence and potential abrupt transitions. Van de Wiel et al (2012) determined the minimum wind speed required for maintaining fully developed turbulence.…”
Section: Introductionmentioning
confidence: 99%